Adsorption Isotherms of Phenol Onto Adsorbents Derived from Egg Shell and Palm-Oil Shell - Asyhar, Rayandra (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2011)
The adsorption isotherms of phenol from aqueous solution onto adsorbents obtained from egg shell (ESA) andpalm shell (PSA) were investigated. The objectives of the investigation were to understand the effect of bothadsorbents on solution pH and to study the adsorption equilibrium of phenol onto the adsorbents. The effect ofadsorbent on pH of solution was studied by shaking the adsorbent of 0.1 to 1.5 g with 100 ml of acidic aqueoussolution for 30 min at room temperature. The adsorption experiments were performed by stirring appropriateamount of adsorbent with 100 ml of 50 mg/l concentration of phenol at constant temperature and pressure. TheLangmuir and Fraundlich adsorption models were applied to experimental data and the isotherm constants werecalculated using linier regression analysis. The results showed that the adsorption capacity of the adsorbentsincreases with increasing of dosage and contact time. Also, pH of solution affected the adsorption isotherm ofphenol, where maximum adsorption was observed at pH values lower than 9.